Bimbingan Konseling Pernikahan Keluarga Islami: Peluang Dakwah Kini dan Mendatang - Ulfatmi Ulfatmi (Intizar, 2015)
Man and women who want to marry should consult with someone who are expert of marriage in the perspective of Islamic law. Consultation in the form of conseling, it is expected that the guidance can build the Islamic family. In addition, it can serve as a model of dakwah about marriage rules in accordance with Islam. A phenomenon that occurs in now days society, before marriage is not begin by consulting with the expert. So that when they build the household there was a commotion until divorce.